Ursolic Acid Enhances Doxorubicin Cytotoxicity on MCF-7 Cells Mediated by G2/M Arrest - Arifin, Ibrahim; Hermawan, Adam; Ikawati, Muthi; Haryanti, Sari; Anindyajati, .; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2012)
Ursolic acid has been widely known to possess biological activity against numerousÂ tumor cell lines. Previous studies revealed its cytotoxicity on several cancer cells Â in vitro byÂ either inducing apoptosis or cell cycle modulation. This Â study was conducted to investigateÂ ursolic Â acidâs Â cytotoxicity Â solely Â and Â in Â combination Â with Â a Â chemotherapeutic Â agent,Â doxorubicin, Â on Â MCF-7 Â breast Â cancer Â cells, Â followed Â by Â observation Â on Â its Â mechanism.Â Cytotoxicity of single and combinational treatment of ursolic acid and doxorubicin on MCF-7Â breast cancer cells were conducted by using MTT assay. Single treatment was then evaluatedÂ by Â determining Â IC50 Â value, Â while Â combinational Â treatment Â was Â evaluated Â by Â analyzing Â cellÂ viability Â and Â evaluating Â combination Â index Â (CI). Â To Â explore Â the Â mechanism Â underlyingÂ cytotoxic Â effect Â on Â respected Â cells, Â further Â analysis Â on Â cell Â cycle Â profile Â of Â single Â andÂ combinational treatment was conducted by flow cytometry. Twenty four hours treatment ofÂ ursolic Â acid Â inhibited Â MCF-7 cellsâ growth with Â IC50 Â value Â of Â 37 Â ÂµM, Â while Â combinationalÂ treatment Â showed Â that Â several Â concentration Â combinations Â of Â ursolic Â acid Â and Â doxorubicinÂ exhibited Â synergism Â of Â cytotoxic Â activity Â on Â MCF-7 Â cells, Â giving Â optimum Â CI Â value Â of Â 0.54.Â Flow cytometric analysis showed that combinational treatment induced G2/M arrest in MCF-7 Â cells. Â These Â results Â show Â that Â ursolic Â acid Â is Â promising Â to Â be Â developed Â as Â either Â singleÂ chemopreventive Â agent, Â or Â as doxorubicinâs co-chemotherapeutic Â agent Â in Â breast Â cancerÂ treatment. Â Observation Â on Â the Â selectivity Â as Â part Â of Â safety Â aspect Â together Â with Â in silico, Â inÂ vitro, and in vivo study on its molecular mechanism should be conducted.Keywords: ursolic acid, doxorubicin,co-chemotherapeutic agent, breast cancer, cell cycle